Optimized first-in first-out pallet load warehouse design - Ramos, Alejandro Emiliano M. (1997)
Among the first-in first-out (FIFO) multi-commodity pallet rack systems developed, the flow-rack is the most efficient. It has the lowest number of aisles, which increases space utilization per unit of warehouse floor space. Pallet loads are automatically indexed forward reducing materials handling Traditional use of flow-rack requires dedicated single stock-keeping units (SKUs). This is necessary to achieve FIFO. Increase in production output of requires a corresponding increase in storage space. If possible, the flow-rack must use every vacant space. However, a packed flow-rack can not enforce FIFO in a fully loaded or packed flow-rack, which can be applied to existing or new warehouse design. A computer simulation using heuristic algorithms is developed. The simulation program analyzes the different flow-rack characteristics like lane depth, number of bays, number and type of product due for retrieval, coordinates of product items for retrieval, number and type of product to be stored, location and size of vacant spaces and coordinates of product items to be stored. This is the basis for determining the coordinates for initial loading and daily production loading of pallets. The loading algorithm of the different product items is needed for ensuring FIFO policy in the packed flow-rack. The program output enumerates the different rectangular dimensions generated and indicates whether each is feasible or not. It contains the daily coordinates for the specific product types with their corresponding serial numbers. The output coordinates guide the warehouseman for storing and retrieving individual pallets to achieve FIFO. Therefore, it is possible to force a packed flow-rack achieve FIFO storage policy and do away with the traditional use of dedicated SKUs. Continuous FIFO flow of stored pallets is enforced with the use of heuristic algorithms. The study showed that optimization of flow-rack space utilization is dependent on the number of product types, number of items per product type, initial load pattern, daily loading arrangement and the flow-rack dimensions. However, the critical factors are the initial loading and daily loading of production. One of the feasible rectangular dimensions generated will be incorporated in the overall production facility. The optimized design will result in reduced storage cost.
Thesis (M.S.)--University of the Philippines, Diliman.
Keywords: Warehouse -- Space utilization -- Mathematical models; Pallets; Storage racks